Developing Quality Of Intra Organizational Interaction Through The Role Of Social Media Interaction Exposure In PT Angkasa Pura II (Persero) - Ivana Rizki Aulia; Suryadi - Poerbo; Andi - Setiawan (Politeknik Negeri Semarang, 2021)
This study aims to analyze the influence of the Role of Social Media Interaction Exposure in building the Quality of Intra-Organizational Interaction in the Human Resources & General Affairs Unit of the Main Branch Office of the Soekarno-Hatta International Airport PT Angkasa Pura II (Persero). The research model is developed based on a literature review. Data collection methods used are interviews and questionnaires. The questionnaire used is the Agree-Disagree Scale with a 10-point scale and the sample collection method used is a total sampling with a sample of 50 employees in the Human Resources & General Affairs Unit of the Main Branch Office of the Soekarno-Hatta International Airport PT Angkasa Pura II (Persero). The analysis technique used is the validity test, reliability test, normality test, heterocedasticity test, multicollinearity test, linearity test, multiple linear regression analysis, t test, F test and coefficient of determination. These results indicate that the Usability (X1) and Information Quality (X2) variables have a significant positive effect on the Quality of Intra-Organizational Interaction (Y). This research only examines the effect of the Role of Social Media Interaction Exposure on the Quality of Intra-Organizational Interaction of BUMN institutions, for further research it can examine the effect of the Role of Social Media Interaction Exposure on Online Engagement variables in addition it can use research objects in other industries such as government agencies. It is recommended that the company must make standard operating procedure (SOP) to set social media used to complete their work.